2019
DOI: 10.1016/j.mechmat.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Modelling surface roughening during plastic deformation of metal crystals under contact shear loading

Abstract: During plastic deformation, metal surfaces roughen and this has a deleterious impact on their tribological performance. It is therefore desirable to be able to predict and control the amount of roughening caused by subsurface plasticity. As a first step, we focus on modelling plastic deformation during contact shearing of an FCC metallic single crystal, employing a finite strain Discrete Dislocation Plasticity (DDP) formulation. This formulation allows us to capture the finite lattice rotations induced in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Deshpande and co-workers [ 21 , 33 ] performed monotonic micro-sliding discrete dislocation plasticity (DDP) simulations to investigate the dislocation structure and surface behaviour under sliding. Nicola and co-workers [ 34 , 35 , 36 ] have also employed the DDP framework to understand the activity of dislocations under multi-asperity, self-affine contact, and the roughness (i.e., the height of the asperities) has been shown to play a key role in the development of plasticity in the subsurface. To the authors’ knowledge, there is no computational framework published for fretting fatigue using DDP.…”
Section: Introductionmentioning
confidence: 99%
“…Deshpande and co-workers [ 21 , 33 ] performed monotonic micro-sliding discrete dislocation plasticity (DDP) simulations to investigate the dislocation structure and surface behaviour under sliding. Nicola and co-workers [ 34 , 35 , 36 ] have also employed the DDP framework to understand the activity of dislocations under multi-asperity, self-affine contact, and the roughness (i.e., the height of the asperities) has been shown to play a key role in the development of plasticity in the subsurface. To the authors’ knowledge, there is no computational framework published for fretting fatigue using DDP.…”
Section: Introductionmentioning
confidence: 99%
“…[27,28]. Several studies of surface roughness and plastic flow have been reported using microscopic (atomistic) models [29], or models inspired by atomic scale phenomena that control the nucleation and glide of the dislocations [30][31][32][33]. These models supply fundamental insight into the complex process of plastic flow, but are not easy to apply to practical systems involving inhomogeneous polycrystalline metals and alloys exhibiting surface roughness of many length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies of surface roughness and plastic flow have been reported using microscopic (atomistic) models [32], or models inspired by atomic scale phenomena that control the nucleation and glide of the dislocations [33][34][35]. These models supply fundamental insight into the complex process of plastic flow, but are not easy to apply to practical systems involving inhomogeneous polycrystalline metals and alloys exhibiting surface roughness on many length scales.…”
Section: Introductionmentioning
confidence: 99%